WEBSITE DESIGN FOR DREAM SHOE PROMOTION - Kurniadin, Rohmad (Arty: Jurnal Seni Rupa, 2019)
Nowadays, the field of business and trade is heavily influenced by the development of information technology, especially in Internet use. With Internet capabilities that can transmit various forms of data such as writing, graphics, images, sound, animation, or even video, many businesses are utilizing this technology by creating a website to promote their business. Marketing by using websites is more efficient and relatively inexpensive compared to conventional methods that require high costs. Dream Shoe, one of the local businesses that provides unique fashion handmade shoes made in Indonesia can utilize this condition to expand the reach of its promotional area by adding a website as one of their promotional media. Website creation can be utilized by the Dream Shoe as a promotional media in the form of information provider about the product owned by Dream Shoes, the website can also serve as an online sales media so that interested people who want to Buy product Dream Shoes can directly buy it through the website without having to come to the store.